Light changes promote distinct responses of plastid protein acetylation marks - Eirich, Jürgen; Boyer, Jean-Baptiste; Armbruster, Laura; Ivanauskaite, Aiste; Torre, Carolina de la; Meinnel, Thierry; Wirtz, Markus; Mulo, Paula; Finkemeier, Iris; Giglione, Carmela (Molecular & cellular proteomics, 2024)
Protein acetylation is a key co- and post-translational modification. However, how different types of acetylation respond to environmental stress is still unknown. To address this, we investigated the role of a member of the newly discovered family of plastid acetyltransferases (GNAT2), which features both lysine- and N-terminal acetyltransferase activities. Our study aimed to provide a holistic multi-omics acetylation-dependent view of plant acclimation to short-term light changes. We found that both the yield and coverage of the N-terminal acetylome remained unchanged in WT and gnat2-KO backgrounds after 2 h of exposure to high light or darkness. Similarly, no differences in transcriptome or adenylate energy charge were observed between the genotypes under the tested light conditions. In contrast, the lysine acetylome proved to be sensitive to the changes in light conditions, especially in the gnat2 background. This suggests unique strategies of plant acclimation for quick responses to environmental changes involving lysine, but not N-terminal, GNAT2-mediated acetylation activity.